2016
DOI: 10.1111/1750-3841.13578
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gallic Acid to Enhance the Antioxidant and Mechanical Properties of Active Fish Gelatin Film

Abstract: This study explores the potential roles of gallic acid in fish gelatin film for improving mechanical properties, UV barrier, and providing antioxidant activities. Glycerol, a common used plasticizer, also impacts on mechanical properties of the film. A factorial design was used to investigate the effects of gallic acid and glycerol concentrations on antioxidant activities and mechanical properties of fish gelatin film. Increasing the amount of gallic acid increased the antioxidant capacities of the film measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…Rise of amplitude at peaks around 1653, 1541, and decline of amplitude at peak around 3273–3275 was shown that there was interaction with hydroxyl group and amino group between gallic acid. The peaks and changing behavior of amplitudes at peaks were found to be similar with gallic acid/fish gelatin film . By the interaction with gallic acid and chickpea‐based flour, formation of new hydrogen and covalent bonds lowered free hydrogen group.…”
Section: Resultsmentioning
confidence: 73%
“…Rise of amplitude at peaks around 1653, 1541, and decline of amplitude at peak around 3273–3275 was shown that there was interaction with hydroxyl group and amino group between gallic acid. The peaks and changing behavior of amplitudes at peaks were found to be similar with gallic acid/fish gelatin film . By the interaction with gallic acid and chickpea‐based flour, formation of new hydrogen and covalent bonds lowered free hydrogen group.…”
Section: Resultsmentioning
confidence: 73%
“…In vitro, CSAT+ ® exerts antioxidant capacity that could be due to the presence of several antioxidant compounds such as gallic, gallotannins, or phenolic compounds [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…This eliminates the need for direct incorporation of active substances in food, which is not a preferable preservation method, as the active substances can be deactivated by other food components, 12 and they may also affect the sensory properties of food products 13 . Previous studies have successfully incorporated various active agents, such as essential oils, 14 gallic acid 15 and fruit peel wastes 16 into FG films and were able to observe improvement in terms of the physical, mechanical and functional properties of the films.…”
Section: Introductionmentioning
confidence: 99%